1995
DOI: 10.1021/bi00029a038
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at Positions 13 and/or 914 in Escherichia coli 16 S Ribosomal RNA Interfere with the Initiation of Protein Synthesis

Abstract: Mutations at positions 13 (U-->A) and/or 914 (A-->U) of Escherichia coli 16S rRNA severely affect cell growth and protein synthesis, when expressed in vivo in a vector encoding an rrn operon under control of an inducible promoter. In vitro assays using extension inhibition indicate that the mutations interfere with the formation of the 30S translational initiation complex, which can account for their effect on cell growth. The two mutations destabilize an adjacent pseudoknot helix in which bases 17-19 pair to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…1). It was previously shown that the U13A mutation causes a small increase in the binding of a probe complementary to the 915-921 region and in the reactivity of G917 to kethoxal (Pinard et al 1995). The increased accessibility of residues within the central pseudoknot indicates that the U13A mutation destabilizes helix 2, making this pseudoknot more flexible.…”
Section: Discussionmentioning
confidence: 99%
“…1). It was previously shown that the U13A mutation causes a small increase in the binding of a probe complementary to the 915-921 region and in the reactivity of G917 to kethoxal (Pinard et al 1995). The increased accessibility of residues within the central pseudoknot indicates that the U13A mutation destabilizes helix 2, making this pseudoknot more flexible.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pUC188G32 (42) and pLRCAT (43) were used for the in vitro transcription of the T4 gene 32 and the gene coding for chloramphenicol acetyl transferase (CAT), 1 respectively, and the mRNAs produced were used for toeprinting and filter-binding studies.…”
Section: Construction Of Plasmids Used In Thismentioning
confidence: 99%
“…The increased reactivity in the synthetic ribosomes (Figure 2) suggests that the structure of the central pseudoknot is less stable than that in natural RNA. The central pseudoknot has been shown to be necessary for efficient translation (Brink et al, 1993;Pinard et al, 1995). Although essential functions are maintained in 30S subunits reconstituted with in Vitrotranscribed RNA (Denman et al, 1989b;Cunningham et al, 1991), these ribosomes have a reduced activity as tested in in Vitro translation assays compared to ribosomes isolated from cells.…”
Section: Discussionmentioning
confidence: 99%